The conceptions of Intersexuality: a critical study of scientific production in Psychology - Barros da Rocha, Maria Laura; Augusta Souto de Oliveira , Adélia (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2022)
The article discusses the conceptions of intersexuality in Psychology, from the completion of meta-synthesis scientific articles, indexed on the virtual platforms SciELO and PePSIC. The methodology is developed in sequential and complementary steps: exploration, refinement, crossing, description and interpretation. The databases were consulted using nine descriptors: intersex, ambiguidade genital, genitalia ambigua, disturbio de diferenciação sexual, DDS, genital ambiguity, ambiguous genitalia, disorder of sex development e DSD. The results indicated 160 articles, published until 2020, of which, at the end of the refinement and crossing stages, 13 were selected and interpreted. The preponderance of theoretical articles, case studies and interviews is asserted as the methodology of choice. The importance of research related to the subject in the field of Psychology is highlighted, whose publications still appear timidly in the analyzed databases. Among the themes discussed in the articles, the following stand out: the invisibility and silence of this population about their condition; the ethical aspects of surgical interventions and the multidisciplinary role in the clinic of intersexuality. Finally, the social and historical aspects related to the constructions of the concept of intersexuality are highlighted, a terminology that marks a break with the terms of the biomedical discursive model, emphasizing the psychosocial dimensions evoked by this expression.